2005
DOI: 10.1103/physrevb.72.060503
|View full text |Cite
|
Sign up to set email alerts
|

Boundary layer model for vortex fingers in type-II superconductors

Abstract: Propagating fingerlike patterns in type-II superconductors are studied through a boundary layer model that takes into account the coupling with the temperature of the sample. By formulating an approach based on an interfacial description for a domain of vortices, we determine the shape-preserving fronts and study the properties and scale of the patterns, such as the fingers' shape and width. We show that the formation and the characteristics of these instabilities are strictly related to the local overheating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 18 publications
(25 reference statements)
0
6
0
Order By: Relevance
“…The last prediction has also been obtained in the boundary layer model allowing calculation of the exact finger shape. 30 The first and the second predictions have already been confirmed experimentally. 10,12 As for the last one, the T dependence of the finger width has not yet been studied.…”
Section: Discussionmentioning
confidence: 66%
“…The last prediction has also been obtained in the boundary layer model allowing calculation of the exact finger shape. 30 The first and the second predictions have already been confirmed experimentally. 10,12 As for the last one, the T dependence of the finger width has not yet been studied.…”
Section: Discussionmentioning
confidence: 66%
“…However, why such avalanches should develop into dendritic patterns is a topic under vivid discussion, and several competing theories were recently proposed. They include a stability analysis taking into account the complicating non-local electrodynamics of thin film superconductors [18,19], a boundary layer model assuming shape-preserving fronts [20], and a shock wave approach [21], all leading to substantially different predictions. In this work we report on the first experi- In the sum image the grey tone regions are those of repeated behavior, whereas colors show where there is no or only partial overlap.…”
mentioning
confidence: 99%
“…10 Like other members, niobium having bcc structure (a=0.3300 nm) with space group Im-3m and jungle-gym type of Fermi surface (FS) has been proven to be an interesting transition metal (TM) for its superconducting and electrical properties. [12][13][14][15][16][17][18][19][20][21] However, its thermoelectric power (S) is relatively poorly understood. 12,13,15,22 Carter et al 13 reported S =0 below its T c and large value of 30 μV/K near 70K.…”
Section: Introductionmentioning
confidence: 99%